PELAKSANAAN TANGGUNG JAWAB ATAS HAK KONSUMEN TERHADAP KLAUSULA PENAWARAN PAKET WISATA DI BALI AMBASSADOR TOUR AND TRAVEL - Komang Ayu Tiara Pratiwi; I Wayan Agus Vijayantera (Fakultas Hukum, Universitas Mahasaraswati Denpasar, 2023)
The purpose of this research is to find out the mechanism and implementation of the responsibilities of Bali Ambassador Tour And Travel regarding the right to the travel package offer clause. The type of legal research used is the empirical legal method. The result of this study is that the implementation of the responsibilities of travel agents is regulated in Article 7 letter g of the Consumer Protection Law. This shows that the travel agency has been responsible for hotel losses that are not in accordance with the contents of the tour package agreement. With this the responsibility given is by way of compensation to consumers. Every problem at Bali Ambassador Tour And Travel will be resolved by negotiation.